2023
DOI: 10.1021/acs.jafc.3c02450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maillard Reaction Products Derived from Cysteine on the Formation of Dimethyl Disulfide and Dimethyl Trisulfide during Storage

Zeyu Zhang,
Bei Wang,
Yanping Cao

Abstract: The effect of Maillard reaction products derived from cysteine on dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS) was evaluated in the ternary mixture (methionine, cysteine, and xylose) and binary mixture (methionine and 2-threitylthiazolidine-4-carboxylic acid) during 56 days storage. Changes in concentrations revealed that the methionine/cysteine/xylose model showed lower concentrations of DMDS and DMTS than those of the binary mixture. Antioxidant ability and labeled isotopomer proportion informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, their common origin may explain the apparent positive relationship between dimethyl disulfide, dimethyl trisulfide, and flavor liking for the roasted samples, where the levels are quite low (Figure 5b). However, recent research has found that dimethyldisulphide and dimethyltrisulphide may be decreased by the presence of Maillard-derived thiols such as 2-methyl-3-furanthiol [40] and this may explain the partial association with consumer flavor liking here and in other studies [28]. For the stewed samples, the very much higher concentrations of dimethyl disulfide and dimethyl trisulfide may confer an off-flavor and have a detrimental effect (Figure 4b).…”
Section: Sulfur Compoundsmentioning
confidence: 62%
See 1 more Smart Citation
“…However, their common origin may explain the apparent positive relationship between dimethyl disulfide, dimethyl trisulfide, and flavor liking for the roasted samples, where the levels are quite low (Figure 5b). However, recent research has found that dimethyldisulphide and dimethyltrisulphide may be decreased by the presence of Maillard-derived thiols such as 2-methyl-3-furanthiol [40] and this may explain the partial association with consumer flavor liking here and in other studies [28]. For the stewed samples, the very much higher concentrations of dimethyl disulfide and dimethyl trisulfide may confer an off-flavor and have a detrimental effect (Figure 4b).…”
Section: Sulfur Compoundsmentioning
confidence: 62%
“…This may have been due to the presence of onions in the stewing mix giving rise to additional sulfur-containing precursors. Their formation has been shown to be inhibited by the presence of anti-oxidants or Maillard-produced thiols [40]. In wine, disulphide and trisulphide formation may be catalyzed by the presence of CuII and FeIII [41].…”
Section: Volatile Compoundsmentioning
confidence: 99%